Aluminum alloy extrusions
Patent Information
- Application Number
- CN202580021245.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-02
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0017] According to embodiments of the present invention, aluminum alloy extrusions with excellent yield strength and crushability can be provided.
Smart Images

Figure CN122935622A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to aluminum alloy extrusion materials. Background Technology
[0002] Historically, there has been a demand for improved occupant safety in vehicles, leading to increased vehicle body strength. On the other hand, against the backdrop of escalating global warming and other issues, the trend towards improving vehicle fuel efficiency is accelerating. It is known that lightweighting the vehicle body is effective in improving fuel economy.
[0003] For this purpose, high-strength 6000 series aluminum alloys are used as automotive components. For example, Patent Document 1 discloses an age-hardening 6000 series (Al-Mg-Si series) aluminum alloy that combines high mechanical properties with high placement stability at room temperature. The aluminum alloy is composed of: 0.6–1 wt% magnesium (Mg), 0.2–0.7 wt% silicon (Si), 0.16–0.7 wt% iron (Fe), 0.05–0.4 wt% copper (Cu), a maximum of 0.15 wt% manganese (Mn), a maximum of 0.35 wt% chromium (Cr), a maximum of 0.2 wt% zirconium (Zr), a maximum of 0.25 wt% zinc (Zn), a maximum of 0.15 wt% titanium (Ti), 0.005–0.075 wt% tin (Sn), and the balance aluminum, and a maximum of 0.05 wt% each, totaling a maximum of 0.15 wt% unavoidable manufacturing impurities. In this case, the Si / Fe weight percentage is less than 2.5, and the Si content is determined according to a prescribed formula.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent No. 7208005 Specification Summary of the Invention
[0007] The technical problem that the invention aims to solve
[0008] In response to recent emissions restrictions, electric vehicles (EVs) are being developed. EVs are equipped with large battery modules protected by frames.
[0009] To achieve vehicle lightweighting, research is underway on the use of extruded 6000 series aluminum alloys in battery module frame materials. For the extruded materials used in the frame, high yield strength (220 MPa level) and excellent crush resistance (no cracking upon crushing) are required to protect the battery module from impacts such as side collisions. However, generally, higher yield strength results in lower crush resistance, making it difficult to improve both simultaneously.
[0010] The 6000 series aluminum alloy disclosed in Patent Document 1 does not focus on extruded materials, therefore no method for simultaneously improving the yield strength and crushability of extruded materials has been studied.
[0011] The present invention was developed in view of such circumstances, and one of its objectives is to provide aluminum alloy extrusions with excellent yield strength and crushability.
[0012] Methods for solving problems
[0013] An aluminum alloy extrusion material contains Si: 0.25-0.39% by mass, Mg: 0.65-0.95% by mass, Fe: less than 0.35% by mass (including 0% by mass), Cu: more than 0% by mass and less than 0.65% by mass, Cr: less than 0.10% by mass (including 0% by mass), and Ti: more than 0% by mass and less than 0.10% by mass, with the balance consisting of Al and unavoidable impurities. The yield strength is greater than 195 MPa, and in cross-sectional SEM observation of the metal microstructure, there are fewer than 25 grain boundary precipitates with a size of more than 50 nm and less than 2 μm in a direction orthogonal to the grain boundaries within a field of view of 90 μm × 120 μm.
[0014] The second embodiment of the present invention is the aluminum alloy extrusion material described in embodiment 1, wherein the Si content is 0.27 to 0.37 by mass.
[0015] The third embodiment of the present invention is the aluminum alloy extruded material described in embodiment 1 or 2, wherein it further comprises Mn: less than 1.0% by mass (including 0% by mass), Zr: less than 0.2% by mass (including 0% by mass), V: less than 0.2% by mass (including 0% by mass), Zn: less than 0.5% by mass (including 0% by mass), Ag: less than 0.1% by mass (including 0% by mass); and Sn: less than 0.15% by mass (including 0% by mass).
[0016] The effects of the invention
[0017] According to embodiments of the present invention, aluminum alloy extrusions with excellent yield strength and crushability can be provided. Attached Figure Description
[0018] Figure 1A This is a cross-sectional SEM image (10000x magnification) of the sample from Test No.2 in the example.
[0019] Figure 1B This is a cross-sectional SEM image (2000x magnification) of the sample from Test No.2 in the example.
[0020] Figure 2 It is a schematic diagram used to illustrate the size of grain boundary precipitates.
[0021] Figure 3Ais a cross-sectional view of a cross section perpendicular to the extrusion direction of the extruded material produced in the example.
[0022] Figure 3B is a cross-sectional view of a cross section perpendicular to the extrusion direction of the extruded material produced in the example.
[0023] Figure 4A is for illustrating the use of Figure 3A a schematic perspective view of a lateral crush test of the extruded material shown in the figure.
[0024] Figure 4B is for illustrating the use of Figure 3B a schematic perspective view of a lateral crush test of the extruded material shown in the figure. DETAILED DESCRIPTION
[0025] The present inventors conducted studies from various angles in order to realize a 6000-series aluminum alloy extruded material excellent in both yield strength and crushability. As a result, the present inventors have found that by limiting the contents of Si and Mg to a narrower range than that of conventional 6000-series aluminum alloys, and reducing the number of grain boundary precipitates present at grain boundaries, an aluminum alloy extruded material capable of achieving high yield strength and high crush performance can be obtained, thereby completing the present invention.
[0026] Hereinafter, details of each requirement specified in the embodiment of the present invention will be described.
[0027] <1. Composition of Components>
[0028] The component composition of the aluminum alloy extruded material according to the embodiment of the present invention includes Si: 0.25 to 0.39 mass%, Mg: 0.65 to 0.95 mass%, Fe: 0.35 mass% or less (including 0 mass%), Cu: more than 0 mass% and 0.65 mass% or less, Cr: 0.10 mass% or less (including 0 mass%), and Ti: more than 0 mass% and 0.10 mass% or less. Further, the balance is preferably Al and unavoidable impurities.
[0029] Hereinafter, each element will be described in detail.
[0030] <Si: 0.25 to 0.39 mass%>
[0031] Si forms a compound phase such as Mg₂Si together with Mg and precipitates, which can improve the strength of the aluminum alloy. In addition, Mg₂Si precipitates at grain boundaries to form grain boundary precipitates.
[0032] When the Si content is less than 0.25 mass%, it is difficult to obtain sufficient yield strength, so the Si content is set to 0.25 mass% or more. The Si content is preferably 0.26 mass% or more, and more preferably 0.27 mass% or more.
[0033] On the other hand, if the Si content is higher than 0.39 mass%, the number of grain boundary precipitates of Mg2Si increases and the crushability decreases, so the Si content is 0.39 mass% or less. The Si content is preferably 0.38 mass% or less, more preferably 0.37 mass% or less, and particularly preferably 0.36 mass% or less.
[0034] <Mg: 0.65 to 0.95 mass%>
[0035] Mg forms a compound phase such as Mg2Si together with Si and precipitates, thereby improving the strength of the aluminum alloy.
[0036] When the Mg content is less than 0.65 mass%, it is difficult to obtain sufficient yield strength, so the Mg content is 0.65 mass% or more. The Mg content is preferably 0.67 mass% or more, more preferably 0.70 mass% or more.
[0037] On the other hand, if the Mg content is higher than 0.95 mass%, the number of grain boundary precipitates of Mg2Si increases and the crushability decreases, so the Mg content is 0.95 mass% or less. The Mg content is preferably 0.93 mass% or less, more preferably 0.90 mass% or less, further preferably 0.88 mass% or less, and particularly preferably 0.80 mass% or less.
[0038] <Fe: 0.35 mass% or less (including 0 mass%)>
[0039] Fe is a main unavoidable impurity in the aluminum alloy. In order not to degrade various properties of the aluminum alloy extruded material, the Fe content is 0.35 mass% or less. The Fe content is preferably 0.30 mass% or less, more preferably 0.27 mass% or less, and particularly preferably 0.25 mass% or less.
[0040] Since Fe is an unavoidable impurity, a smaller content thereof is more preferable. Therefore, the lower limit of the Fe content is 0 mass%, but reducing it to less than 0.05 mass% imposes a heavy cost burden. Therefore, the lower limit of the Fe content may be 0.05 mass%, may be 0.10 mass%, may be 0.15 mass%, or may be 0.18 mass%.
[0041] <Cu: more than 0 mass% and 0.65 mass% or less>
[0042] Cu is an element that improves the strength of the aluminum alloy extruded material. In order to exhibit this effect, the Cu content exceeds 0 mass%. The Cu content is preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and particularly preferably 0.12 mass% or more.
[0043] On the other hand, if the Cu content is higher than 0.65 mass%, the extrudability and corrosion resistance will be reduced, so the content is set to 0.65 mass% or less. The Cu content is preferably 0.30 mass% or less, more preferably 0.20 mass% or less, and particularly preferably 0.18 mass% or less.
[0044] <Cr: 0.10 mass% or less (including 0 mass%)>
[0045] Cr is an unavoidable impurity in the aluminum alloy. When the Cr content is high, galling tends to occur during the extrusion process, so the content is set to 0.10 mass% or less.
[0046] Since Cr is an unavoidable impurity, a lower content is more preferable. Therefore, the lower limit of the Cr content is 0 mass%, but reducing the content to less than 0.01 mass% imposes a large cost burden. Therefore, the lower limit of the Cr content may be 0.01 mass%, 0.03 mass%, or 0.05 mass%.
[0047] <Ti: more than 0 mass% and 0.10 mass% or less>
[0048] Ti has the effect of improving the formability of the extruded material. To achieve this effect, the Ti content is set to more than 0 mass%. The Ti content is preferably 0.01 mass% or more, more preferably 0.02 mass% or more.
[0049] On the other hand, if the Ti content is higher than 0.10 mass%, its effect is saturated, so the content is set to 0.10 mass% or less. The Ti content is preferably 0.08 mass% or less, more preferably 0.06 mass% or less, and particularly preferably 0.05 mass% or less.
[0050] <Unavoidable impurities>
[0051] In one embodiment of the present invention, the balance is preferably aluminum and unavoidable impurities. As unavoidable impurities, mixing of elements brought in due to conditions of raw materials, materials, manufacturing equipment and the like is permitted. The content of unavoidable impurity elements other than the above elements is controlled within the range specified for 6000-series alloys by JIS standards and the like. Specific examples of the unavoidable impurity elements include Ni, In, Ga, B, Na, Ca, Sc and the like. The content of each of these elements is preferably 0.05 mass% or less, and the total content thereof is preferably 0.15 mass% or less.
[0052] Further, for example, Fe, of which a lower content is usually preferred, is an unavoidable impurity, but there are elements whose composition ranges are separately specified as described above. Therefore, in this specification, the term "unavoidable impurities" refers to a concept excluding elements whose composition ranges are separately specified.
[0053] <Other Elements>
[0054] The aluminum alloy plate of this embodiment may contain elements other than those described above, such as the elements listed below. The permissible amounts of these elements from scrap, molten raw materials for ingots, etc., are limited to the following maximum amounts; if these amounts are within these limits, the effects of the invention will not be hindered even with aggressive addition. Furthermore, there are no lower limits for each content, including 0%.
[0055] Mn: less than 1.0% by mass, Zr: less than 0.2% by mass, V: less than 0.2% by mass, Zn: less than 0.5% by mass, Ag: less than 0.1% by mass, Sn: less than 0.15% by mass
[0056] <2. Yield Strength>
[0057] The aluminum alloy extruded material of the embodiments of the present invention has a yield strength (average yield strength) of 195 MPa or higher. This is equivalent to a yield strength of 220 MPa or higher (220 ± 25 MPa). By having such a high yield strength, when used as a frame material for battery modules, it can protect the battery modules from impacts.
[0058] To achieve the desired yield strength, it is important to control the composition (especially to ensure that the Si content is above 0.25% by mass and the Mg content is above 0.65% by mass).
[0059] The yield strength was determined as follows.
[0060] Tensile test specimens of JIS 13B or JIS 5 were collected from aluminum alloy extrusions and subjected to tensile testing at room temperature to determine the 0.2% yield strength.
[0061] Prepare multiple (e.g., 2 to 5) test pieces with the tensile direction parallel to the extrusion direction (L direction). Perform tensile tests according to the test methods for metallic materials specified in JIS Z 2241:2011. Calculate the arithmetic mean of the yield strength values obtained from multiple (e.g., 2 to 5) tensile tests to obtain the yield strength (average yield strength) of the aluminum alloy extruded material.
[0062] <3. Number of grain boundary precipitates>
[0063] The aluminum alloy extruded material of the embodiments of the present invention can exhibit excellent crushability by reducing the number of grain boundary precipitates of a specified size.
[0064] During their intensive research, the inventors discovered that the dimensions in the direction orthogonal to the grain boundary 20 (refer to...) Figure 2Grain boundary precipitates 10 with a size of less than 2 μm affect the crushability of aluminum alloy extrusions. Based on this insight, further research was conducted, and the results showed for the first time that, in cross-sectional SEM observation of the metal microstructure, crushability can be improved by reducing the number of grain boundary precipitates 10 with a size of 50 nm or more and less than 2 μm in a direction orthogonal to the grain boundary 20 within a 90 μm × 120 μm field of view to 25 or fewer.
[0065] Hereinafter, “the size of grain boundary precipitate 10” refers to the size of grain boundary precipitate 10 in the direction orthogonal to grain boundary 20.
[0066] In order to control the size and number of grain boundary precipitates 10 within the desired range, it is important to control the composition of the aluminum alloy (especially to keep the Si content below 0.39% by mass and the Mg content below 0.95% by mass) and to control the cooling rate after extrusion during manufacturing.
[0067] The number of grain boundary precipitates was determined by cross-sectional SEM observation within a 90 μm × 120 μm field of view. Figure 1B (Magnification 2000x). Grain boundary precipitates 10 typically take the form of elongated shapes extending along grain boundaries 20. Figure 1A ).
[0068] The grain boundary precipitate 10 being measured is only considered as a grain boundary precipitate 10 with a size of less than 2 μm in a direction orthogonal to the grain boundary 20. Figure 2 That is, grain boundary precipitates 10 with a size exceeding 2 μm are not included in the measurement (and are not counted as grain boundary precipitates 10). In addition, based on the resolution of the SEM device, the lower limit of the size of the grain boundary precipitates 10 orthogonal to the grain boundary 20 is 50 nm.
[0069] Figure 2 The direction orthogonal to grain boundary 20 is determined based on the premise that grain boundary 20 is straight, but in reality, grain boundary 20 is often not straight. Figure 1A , Figure 1B At this point, the "direction orthogonal to grain boundary 20" is determined as follows.
[0070] In the cross-sectional SEM image, a point is taken on the grain boundary near the center of the grain boundary precipitate 10 whose size is to be measured, and a tangent line is drawn from this point on the grain boundary. The direction orthogonal to this tangent line is considered the "direction orthogonal to the grain boundary 20," and the size of the grain boundary precipitate 10 is confirmed. Figure 1B If it is difficult to determine the size of the grain boundary precipitate 10 at the observation magnification (2000x), the magnification can be increased (e.g., 10000x) for cross-sectional SEM observation to confirm the size of the grain boundary precipitate 10. Figure 1A ).
[0071] Cross-sectional SEM observation used sections parallel to the extrusion direction (L direction) and thickness direction (ST direction) as observation planes, setting three arbitrary fields of view around 1 / 4t of the plate thickness. Within each field of view, the number of grain boundary precipitates 10 with dimensions greater than 50 nm and less than 2 μm in the direction orthogonal to the grain boundary 20 was measured. When observing the observation plane in BSE (Back Scattered Electron) mode, the grain boundary precipitates 10 were observed as black, elongated particles existing along the grain boundary 20. The total number of grain boundary precipitates 10 calculated in each field of view was divided by 3 to obtain the average number of grain boundary precipitates 10 in the aluminum extrusion.
[0072] <4. Manufacturing Method>
[0073] In the method for manufacturing aluminum alloy extruded material according to an embodiment of the present invention, an ingot of aluminum alloy having the above-described composition is cast, homogenized, and then extruded at an extrusion temperature. After cooling the extruded product, it is subjected to artificial aging treatment, thereby obtaining an aluminum alloy extruded material having the desired characteristics.
[0074] It should be noted that cooling after extrusion molding is usually carried out by water cooling (average cooling rate 5000–30000 °C / min (83–500 °C / sec)). To reduce manufacturing costs, the inventors investigated cooling after extrusion molding using fan air cooling (average cooling rate 50–300 °C / min (0.83–5 °C / sec)). However, if the cooling rate after extrusion molding slows down, the number of grain boundary precipitates increases, raising concerns about reduced compressibility.
[0075] The inventors' research shows that by controlling the composition of the aluminum alloy to the composition specified in the embodiments of the present invention (in particular, making the Si content less than 0.39% by mass), the increase in the number of grain boundary precipitates is suppressed even when air-cooled, thus achieving excellent crushability.
[0076] This manufacturing method enables the production of aluminum alloy extrusions with a yield strength of over 195 MPa and excellent crushability.
[0077] Example
[0078] The following examples illustrate the implementation of the present invention in more detail. The implementation of the present invention is not limited to the following examples; appropriate modifications may be made to achieve the objectives described above and below, and all such modifications are included within the technical scope of the embodiments of the present invention.
[0079] <Sample Making>
[0080] The aluminum alloy billet ingots with the compositions shown in Table 1 were homogenized at 520°C for 4 hours, then heated to 500°C and extruded at a rate of 6 m / min. Cooling after extrusion was done by fan air cooling. The extrusion ratio was 4:4 for tests No. 1–5, and 5:4 for No. 6 and 7. Furthermore, the extrusion shape (cross-sectional shape) was as follows for No. 1–5: Figure 3A The cross-sectional shape shown is as follows in experiments No. 6 and 7: Figure 3B The cross-sectional shape is shown. After fan-air cooling, artificial aging treatment (T5 treatment) is performed. Tensile and transverse crush tests are conducted on the artificially aged samples.
[0081] Tensile Test
[0082] From the specified location of the sample after artificial aging ( Figure 3A and Figure 3B Two JIS 13B test pieces were taken from the test materials 31 and 32 (the portions labeled "tensile test pieces") and subjected to tensile tests at room temperature. The test pieces were prepared with the tensile direction parallel to the compressive direction (L direction). Tensile tests were performed according to the test methods for metallic materials specified in JIS Z 2241:2011, and the tensile strength, yield strength, and elongation were determined. Two measurements were performed, and the arithmetic mean of the results is shown in Table 2.
[0083] <Transverse crush test>
[0084] The artificially aged samples were cut into 200mm lengths along the compression direction (L direction) and used as test materials 31 and 32 for the transverse crush test. Figure 4A , Figure 4B Using a 30-ton universal testing machine, test materials 31 and 32 are placed on the platform, and the indenter 40 is pressed down from the upper surface of the test materials 31 and 32 to conduct a transverse crushing test. The displacement of the indenter 40 during the test is within the range of test No. 1 to 5. Figure 4A The displacement was 27 mm (equivalent to 50% of the height of the test material 31) in tests No. 6 and 7. Figure 4B The displacement is 35 mm (equivalent to 40% of the height of test material 32). Observe the test materials 31 and 32 after the test and visually inspect for crushing cracks. No cracks are evaluated as qualified (〇), and cracks are evaluated as unqualified (×). Record the evaluation results in the "Crushability" column of Table 2.
[0085] <Measurement of Grain Boundary Precipitates>
[0086] For samples after artificial aging, SEM observation of cross-sections parallel to the extrusion direction (L direction) and thickness direction (ST direction) was performed. Cross-sectional SEM observations were conducted in BSE (Back Scattered Electron) mode. Three fields of view were randomly selected near 1 / 4 t of the plate thickness for observation at 2000x magnification. Figure 1B The observation area for each field of view is 90 μm (ST direction) × 120 μm (L direction). Grain boundary precipitates 10 on the confirmed grain boundaries 20 within the observation area were further observed at 10000x magnification. Figure 2 Grain boundary precipitates 10 were observed as elongated, black particles present along grain boundaries 20. Figure 1A ). Count the grain boundary precipitates 10 with a size greater than 50 nm and less than 2 μm in the direction orthogonal to grain boundary 20 (in order to ). Figure 1B The number of grain boundary precipitates 10 (indicated by the arrow) is also considered. Furthermore, the lower limit of the size of the grain boundary precipitates 10 being measured is determined based on the detection limit of the SEM device (approximately 50 nm). The total number of grain boundary precipitates 10 calculated in each field of view is divided by 3 to obtain the average number of grain boundary precipitates 10 in that sample. The results are shown in Table 3.
[0087] [Table 1]
[0088]
[0089] [Table 2]
[0090]
[0091] [Table 3]
[0092]
[0093] Samples from tests No. 1 and 7 both meet the requirements specified in the embodiments of the present invention, exhibiting high yield strength (above 195 MPa) and excellent crushability.
[0094] Samples in tests No. 2, 5, and 6 failed the crushability test because the Si content was too high, resulting in an average number of grain boundary precipitates exceeding 25 within the field of view.
[0095] Samples in tests No. 3 and 4 had yield strengths lower than 195 MPa due to insufficient Si content.
[0096] This application is accompanied by a priority claim based on Japanese Patent Application No. 2024-059688, filed on April 2, 2024. This specification is incorporated herein by reference to Japanese Patent Application No. 2024-059688.
[0097] Explanation of reference numerals in the attached figures
[0098] 10 Grain boundary precipitates
[0099] 20 Grain boundaries
[0100] Test materials used in experiments 31 and 32
[0101] 40 pressure head
Claims
1. An aluminum alloy extrusion material, comprising Si: 0.25–0.39% by mass Mg: 0.65–0.95% by mass Fe: less than 0.35% by mass and containing 0% by mass Cu: above 0% by mass and below 0.65% by mass Cr: less than 0.10% by mass and containing 0% by mass and Ti: greater than 0% by mass and less than 0.10% by mass The balance consists of Al and unavoidable impurities. Yield strength above 195 MPa In cross-sectional SEM observation of metal microstructure, there are fewer than 25 grain boundary precipitates with a size of 50 nm or more and 2 μm or less that exist in a field of view of 90 μm × 120 μm and are orthogonal to the grain boundaries.
2. The aluminum alloy extruded material according to claim 1, wherein, The Si content is 0.27–0.37% by mass.
3. The aluminum alloy extruded material according to claim 1, wherein, Also includes Mn: less than 1.0% by mass and containing 0% by mass Zr: less than 0.2% by mass and including 0% by mass V: less than 0.2% by mass and including 0% by mass Zn: less than 0.5% by mass and containing 0% by mass Ag: Less than 0.1% by mass and including 0% by mass, and Sn: less than 0.15% by mass and containing 0% by mass.
4. The aluminum alloy extruded material according to claim 2, wherein, Also includes Mn: less than 1.0% by mass and containing 0% by mass Zr: less than 0.2% by mass and including 0% by mass V: less than 0.2% by mass and including 0% by mass Zn: less than 0.5% by mass and containing 0% by mass Ag: Less than 0.1% by mass and including 0% by mass, and Sn: less than 0.15% by mass and containing 0% by mass.
Citation Information
Patent Citations
Computer program, method and server device
JP2024059688A